On the relations among the language, speech and music - Uličný, Oldřich (Bohemica Olomucensia, 2013)
Using methods of functional and structural analysis the author observes that sound units and their systemic relations are the core of analogy among language, speech and music. Structure of sound unit is analogical or parallel in details only - because music is communicative mean with the esthetic value but language primary not. Language is parallel to music secondary only, approaching music in poetry and singing.